2022
DOI: 10.3390/ijms23126488
|View full text |Cite
|
Sign up to set email alerts
|

Neurosecretory Protein GL Promotes Normotopic Fat Accumulation in Male ICR Mice

Abstract: Neurosecretory protein GL (NPGL) is a small secretory protein identified in the hypothalamus of birds and mammals. We recently reported that NPGL exerts obesogenic effects in obesity-prone C57BL6/J mice. However, whether NPGL elicits adiposity in different mouse strains is poorly understood. In this study, we generated transgenic mice overexpressing Npgl using the ICR strain (Npgl Tg mice) to elucidate the obesogenic effects of NPGL in different strains. Npgl Tg mice showed increased white adipose tissue (WAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These mechanisms are regulated by neuropeptides and/or hormones (Schwartz et al, 2000). NPGL and NPGM have been reported as novel neuropeptides related to energy metabolism in rodents and chickens (Iwakoshi-Ukena et al, 2017; Shikano et al, 2019; Kato et al, 2021; Narimatsu et al, 2022a, b). NPGL and NPGM have no similarity to other neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms are regulated by neuropeptides and/or hormones (Schwartz et al, 2000). NPGL and NPGM have been reported as novel neuropeptides related to energy metabolism in rodents and chickens (Iwakoshi-Ukena et al, 2017; Shikano et al, 2019; Kato et al, 2021; Narimatsu et al, 2022a, b). NPGL and NPGM have no similarity to other neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
“…In GIFT tilapia ( Oreochromis niloticus ), NPGL mRNA-containing cells are localized in the anterior periventricular pretectal nucleus of the anterior preoptic area and lateral tuberal nucleus of the hypothalamus (Huang et al, 2022). We previously showed that NPGL induces food intake and fat accumulation in rats, mice, and chicks (Iwakoshi-Ukena et al, 2017; Matsuura et al, 2017; Shikano et al, 2019; Narimatsu et al, 2022a, b). These results suggest that NPGL is a novel regulator of energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…RNA isolation and qRT-PCR were performed as previously reported [23,30,31]. Total RNA was isolated using the TRIzol reagent (Life Technologies, Carlsbad, CA, USA).…”
Section: Quantitative Reverse Transcriptase Pcr (Qrt-pcr)mentioning
confidence: 99%